Antimicrobial mechanism of semi-bionic extracts of three traditional medicinal plants—Rheum palmatum L., Scutellaria baicalensis Georgi, and Houttuynia cordata Thunb—That can be used as antibiotic alternatives - Jiang, Hong; Bai, Zixia; Xu, Ziheng; Sun, Jian; Françoise, Hatungimana; Luan, Zuxiang; Wang, Hongjun (Frontiers in Veterinary Science, 2023)
The Chinese traditional medicinal plants Rheum palmatum L., Scutellaria baicalensis Georgi, and Houttuynia cordata Thunb in a ratio of 108:65:27 form a compound named Dahuang Qinyu San (DQS), which inhibits and kills Escherichia coli and Salmonella to a certain extent in fish and shrimp aquaculture environments. The active ingredients quercetin, emodin, baicalin, and aloe-emodin are obtained from the semi-biomimetic extract of DQS (SEDQS). However, the antibacterial mechanism of SEDQS against Salmonella is still unclear. This study used the microwell-plate method to determine the Minimum Inhibitory Concentration (MIC) of SEDQS against Salmonella enteritidis (S. enteritidis) isolated from geese. In addition, the effect of SEDQS on the growth curve, respiratory metabolic system, cell wall, soluble protein, and nucleic acid in bacterial liquid of S. enteritidis was detected by spectrophotometer and reagent kit. The effects of SEDQS on S. enteritidis DNA, binding gel blocking, virulence gene expression, and pathogenicity-related proteins were determined by gel electrophoresis, SDS–PAGE, and fluorescence quantitative PCR. The study found that a concentration of 1/4 MIC−2 MIC (2.27–18.2 mg/ml) SEDQS can significantly inhibit the normal growth of S. enteritidis, destroy the cell membrane structure of bacteria resulting in the leak of nucleic acid, protein, and other contents (P < 0.01). It also significantly inhibited the activities of succinate dehydrogenase (SDH) and malate dehydrogenase (MDH; P < 0.01) in a concentration-dependent manner. When the concentration of SEDQS was 1/2 MIC to 2 MIC (4.55–18.2 mg/ml), the expression levels of gyrB, fimA, filC, spvR, Hcp, and vgrG virulence genes (P < 0.01) all decreased by more than 31, 11, 18, 30, 34, and 21% respectively compared with the control group. SEDQS could significantly inhibit the expression of six virulence genes and play an important role in the pathogenicity of the S. enteritidis infected host. The SEDQS could exert antibacterial pharmacological effects by inhibiting the growth and metabolism of S. enteritidis and inhibiting the expression of major virulence factors. It has potential application value as an antibiotic alternative.